(untitled) (Research, Society and Development, 2020)
This work aimed to characterize the physicochemical parameters and technological properties of breasts from poultry with WS and compare them with normal breasts to evaluate breast quality. Poultry breast fillets (10 normal and 10 carcasses with WS) were White Striping (WS) is a major problem that compromise the quality of the meat. Occurrence of WS on the surface of chicken breasts impairs the visual appearance and consequently decreases consumer acceptance causing damage to the industrial sector. obtained from a slaughterhouse. Then they were weighed, packaged and stored in the freezer at -20°C until analysis of: pH, moisture, protein, lipids, lipid oxidation, warmed-over flavor (WOF), water holding capacity (WHC), cooking loss (CL), exudate protein content (EP) and myofibrillar fragmentation index (MFI) of proteins. The physicochemical characteristics and technological parameters of poultry breasts with WS compromised the quality of the product when compared to the normal breast showing heavier breasts, increasing moisture, lipid content, lipid oxidation and WOF, reduction in total protein content and WHC and an increase in CL, EP content and MFI of proteins. Therefore, this myopathy showed changes in the physical and chemical parameters that can compromise the technological and sensory aspects of meat products, affecting their quality.